2010
DOI: 10.1089/jwh.2009.1706
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptive Use Among Women in the Military and the General U.S. Population

Abstract: Objective: To compare oral contraceptive (OC) use during a 12-month period among women aged 18-39 years in the U.S. military and the general U.S. population using data from the Military Health System Management Analysis and Reporting Tool (M2) and the National Health and Nutrition Examination Survey (NHANES), respectively. Methods: OC use was age adjusted to the 2000 U.S. Census population. Comparisons between the military (n ¼ 83,181) and the general population (unweighted n ¼ 360), as well as between the mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…Using the Military Health System Management Analysis and Reporting Tool, we retrieved medical encounters data and medication fill histories. The Military Health System Management Analysis and Reporting Tool is a powerful tool that has been used in health care administration, [12][13][14] use, 12,15,16 and outcomes research. 17,18 The data include the full spectrum of clinical care regardless of point-of-service location or affiliation 12,14,19 : 1.…”
Section: Methodsmentioning
confidence: 99%
“…Using the Military Health System Management Analysis and Reporting Tool, we retrieved medical encounters data and medication fill histories. The Military Health System Management Analysis and Reporting Tool is a powerful tool that has been used in health care administration, [12][13][14] use, 12,15,16 and outcomes research. 17,18 The data include the full spectrum of clinical care regardless of point-of-service location or affiliation 12,14,19 : 1.…”
Section: Methodsmentioning
confidence: 99%
“…Using the Military Health System Management Analysis and Reporting Tool (M2), we retrieved all inpatient and outpatient medical encounters, diagnoses, and drug fill histories. The M2 database is a powerful tool that has been used in administrative and leadership decision making as well as in research …”
Section: Methodsmentioning
confidence: 99%
“…The M2 database is a powerful tool that has been used in administrative and leadership decision making as well as in research. [13][14][15][16][17] The M2 database encompasses the full spectrum of clinical care including outpatient electronic medical records, inpatient electronic medical records, medical benefits claims data, laboratory data, and pharmacy data. Outpatient medical records contain all outpatient service activities.…”
Section: Methodsmentioning
confidence: 99%
“…A large study (n=83 181) that used data from the US Military Health System Management Analysis and Reporting Tool reported that overall OC use was 34% among servicewomen aged 18–39 years, and OC use increased with age 20. Of note, none of these studies assessed risk factors for non-adherence of OC.…”
Section: Discussionmentioning
confidence: 99%